“Beauty, Blood, and Boundaries: Interrogating Genre and Morality in ‘Haunting Adeline’ Novel written by H.D. Carlton Using Sigmund Freud’s Psychoanalytic Theory” - Satria Raditiyanto; Amina Amina; Purwadi Purwadi (Journal of Literature Language and Academic Studies, 2026)
Purpose – This Literature Research will analyze the themes of beauty, violence, and moral tension in H. D. Carlton's novel Haunting Adeline using Sigmund Freud's psychoanalytic theory. Methodology – By focusing on key Freudian concepts such as the id, ego, superego, repression, and the life–death drives, this study examines how the novel portrays desire and boundary-breaking behavior within the dark romance genre. Findings – Through close reading, the analysis shows how the characters' actions reflect unconscious impulses that challenge traditional ideas of morality, consent, and emotional control. Novelty – The results suggest that the novel's blend of attraction and danger creates a space where psychological conflict becomes central to the reader's experience. Significance – Overall, this study argues that Haunting Adeline not only pushes the limits of romantic storytelling but also highlights how human behavior is shaped by complex inner forces, making it a meaningful text for understanding the relationship between genre, morality, and the unconscious mind.